STUDY OF PERCEPTIONS ON HYBRID LEARNING IN THE TEACHING OF ENGLISH AT MTSN 4 BONE DURING THE COVID-19 PANDEMIC - Mutmainnah Mutmainnah; Samtidar Samtidar; Chairil Anwar Korompot (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aimed to find out the perceptions of teachers and students about hybrid learning in the teaching of English. The researchers used a qualitative method. The samples for this research are 10 students and all of the English teachers. This study uses triangulation which is interview, observation and documentation. The result of this study are, 1) The teacher has a positive perception about hybrid learning that is make them could minimize the weaknesses of online learning; 2) And the students also have a positive perception about hybrid learning that make them easier to understand the material that the teacher gave to them in online learning; and 3) They did hybrid learning without ignoring the health protocol, so that the teachers setting hybrid learning corresponding health protocol. In the side of beneficial, all teachers feel that hybrid learning is the one of solution that the teacher used to minimize the weaknesses of online learning. Some students also still like online learning.